The Role of Global Value Chains for Worker Tasks and Wage Inequality - Piotr Lewandowski; Karol Madoń; Deborah Winkler (Institute of Labor Economics (IZA), 2023)
This paper studies the relationship between global value chain (GVC) participation, worker-level routine task intensity, and wage inequality within countries. Using unique survey data from 38 countries, we find that higher GVC participation is associated with more routine-intensive work, especially among workers in offshorable occupations. This relationship is particularly strong in industry and in countries at lower development levels. As higher routine task intensity links with to wages, this indirectly widens within-country wage inequality. However, GVC participation directly contributes to reduced wage inequality, except in the richest countries. Overall, GVC participation is negatively associated with wage inequality in most low- and middle-income countries that receive offshored jobs, and positively in high-income countries that offshore jobs.
Keywords: J21; J24; J31; F66; 330; routine task intensity; global value chains; globalisation; cross-country division of work; wage inequality